Italian football - Baroncelli, A.; Lago, U. (Journal of Sports Economics, 2006)
The Italian football industry has recently grown at a pace that was never experienced before, boosted by the entrance of pay TV into the business. Nevertheless, Italian football has recently sunk into a deep financial crisis, which has caused bankruptcy for some clubs and strong downsizing for others. At the end of the 2002-2003 football season, the aggregate net loss for Serie A was larger than [UNKNOWN] 400 million, more than one third of total turnover. In the present article, the authors analyze some data from Italian football, discuss the reasons for the financial crisis, and propose some remedies.